2007
DOI: 10.1523/jneurosci.5564-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's-Type Amyloidosis in Transgenic Mice Impairs Survival of Newborn Neurons Derived from Adult Hippocampal Neurogenesis

Abstract: Alzheimer's disease (AD) is characterized by severe neuronal loss in several brain regions important for learning and memory. Of the structures affected by AD, the hippocampus is unique in continuing to produce new neurons throughout life. Mounting evidence indicates that hippocampal neurogenesis contributes to the processing and storage of new information and that deficits in the production of new neurons may impair learning and memory. Here, we examine whether the overproduction of amyloid-␤ (A␤) peptide in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(157 citation statements)
references
References 72 publications
10
144
3
Order By: Relevance
“…2 and 4). Notably, impaired neurogenesis, and specifically the survival and differentiation of neuronal progenitors, have been reported in mouse models of AD [230,231]. Thus, the activation of differentiation programs (neuroD1, bdnf) in pathological brains might be a promising strategy in AD.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 4). Notably, impaired neurogenesis, and specifically the survival and differentiation of neuronal progenitors, have been reported in mouse models of AD [230,231]. Thus, the activation of differentiation programs (neuroD1, bdnf) in pathological brains might be a promising strategy in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent work demonstrated that the FCs LEC to DG projecting neurons form a major input to the new born neurons of this hippocampal area [50]. Alterations of their firing patterns during early AD symptomatology could contribute to altered neurogenesis [49] and the development of cognitive deficits [9].…”
Section: Functional Implications Of Altered Scs and Fcs Firing Duringmentioning
confidence: 99%
“…An agedependent decrease in SGZ proliferation was also observed in mice transgenic for human V717F mutant APP, a model of AD with age-dependent accumulation of Aβ42-containing plaques (Donovan et al, 2006). Impaired neuronal differentiation of NPCs was also confirmed in transgenic mice coexpressing two or three mutated genes of APP and PS1 (Verret et al, 2007;Zhang et al, 2007;Rodríguez et al, 2008;Demars et al, 2010). Nevertheless, conflicting observations have been obtained from PDGF-APPswe,ind mice (J20), which express the Swedish and Indiana APP mutations of APP.…”
Section: Neurogenesis Under Pathological Conditionsmentioning
confidence: 90%